Pengaruh Penambahan Threshold Inspiratory Muscle Training Praoperasi Terhadap Postoperative Pulmonary Complication Pasca Bedah Ganti Katup Jantung - Erna Setiawati; Ronni Untung Handayanto; Sri Wahyudati (Indonesian Journal of Physical Medicine & Rehabilitation, 2020)
ABSTRACT Introduction: Cardiac surgery has been improved patient’s outcome with cardiac valve anomaly. There was 111 cardiac valve replacement surgery performed in Kariadi General Hospital Semarang in 2018.Postoperative pulmonary complication (PPC) is the most common complication in this procedure compared to cardiac complication which are thought caused by the disruption of normal respiratory function as a result from surgical and anesthetic procedure. Additional preoperative threshold inspiratory muscle training (Threshold IMT) has been considered as an ef fective intervention to reduce PPC. Methods: This is a quasi experimental study with main reason to know the role of Threshold IMT on PPC incidences. Subjects in the intervention group were given routine conventional rehabilitationexercises according to Clinical Practice Guide (PPK) with additional of Threshold IMT, which applied based on research protocols, while control group did convention al rehabilitation exercises only. Results: 18 subjects were divided into intervention group (n=9), and control group (n=9), PPC incidences (Intervention group n=2, control group n=7) were analyzed statistically using Chi-squared test andshowed significant differences (Fisher exact test p=0.02 with α=0.05). Conclusion: Additional of Threshold IMT preoperative may reduce the incidence of PPC on heart valve replacement surgery.Keywords: Postoperative pulmonary complication (PPC), Threshold inspiratory muscle training (Threshold IMT)